Pengaruh Model Student Teams Achivement Division (STAD) Terhadap Prestasi Belajar Siswa - Aufa, Minzani; Amrul Haq, Akhmad Liana (Universitas Muhammadiyah Magelang, 2020)
The research objective was to determine how much influence the application of the Student Teams Achievement Divisions has on student achivement and understanding of the consept student learning material. This research uses the Action Research method which is carried out in two cycles, in each cycle carrying out the planning, application, observation, and reflection stages. The subjects of this research were 25 students of class V MIM 1 Bumirejo. The data analysis technique uses descriptive quantitative and data obtained from the test. The result showed the level of attainment of student learning completeness information in cycle 1 was 44%, in cycle 2 it was 84 %, meaning that the application of the Student Teams Achievement Divisions type of cooperative learning model increased by 40%. In the description of the test results for understanding the concept of learning materials based on the achievement of the KKM, students experienced a significant increase in the concept of learning material.